Predictive performance of critical illness scores and procalcitonin in sepsis caused by different gram-stain bacteria (Clinics, 2021)
OBJECTIVES: To compare the early and late predictive values of several critical illness scores (CISs) and biomarkers in sepsis-3 patients with bloodstream infections (BSIs) and to identify the prognostic value of procalcitonin (PCT) for different gram-stain bacteria infections.METHODS: Patients with at least one positive blood culture within 24h of emergency department admission and with a final diagnosis of sepsis/septic shock were enrolled. CISs were calculated based on the first parameters on the day of admission. The receiver operating characteristics curve was used to analyze the predictive value of CISs and biomarkers for early and late mortality.RESULTS: Of 834 enrolled patients with sepsis-3, death occurred in 214 patients within 28 days and in 273 patients within 60 days. Compared with biomarkers, CISs showed a significantly higher area under the curve (AUC) in the prediction of early and late mortality (p<0.01), especially for patients with GNB infection. The Sequential Organ Failure Assessment score showed a higher AUC for predicting early mortality than the Mortality in Emergency Department Sepsis score (p=0.036). Compared with GNB infections, the AUC values of the PCT for gram-positive bacteria (GPB) infections were higher for predicting early or late mortality; PCT showed higher AUC than high-sensitivity C-reactive protein and white blood cells for predicting early mortality (p<0.05).CONCLUSIONS: CISs were more advantageous in the assessment of early and late prognosis, especially for patients with GNB infections; however, for sepsis with GPB infection, PCT can be used for the prediction of early mortality.